Heparan sulphate proteoglycans are essential for the myeloma cell growth activity of EGF-family ligands in multiple myeloma - Mahtouk, Karène; Cremer, Friedrich Walter; Rème, T.; Jourdan, M.; Baudard, M.; Moreaux, J.; Requirand, G.; Fiol, G.; De Vos, J.; Moos, Marion; Quittet, P.; Goldschmidt, Hartmut; et al. (Oncogene, 2006)
The epidermal growth factor (EGF)/EGF-receptor (ErbB1-4) family is involved in the biology of multiple myeloma (MM). In particular, ErbB-specific inhibitors induce strong apoptosis of myeloma cells (MMC) in vitro. To delineate the contribution of the 10 EGF-family ligands to the pathogenesis of MM, we have assessed their expression and biological activity. Comparing Affymetrix DNA-microarray-expression-profiles of CD138-purified plasma-cells from 65 MM-patients and 7 normal individuals to those of plasmablasts and B-cells, we found 5/10 EGF-family genes to be expressed in MMC. Neuregulin-2 and neuregulin-3 were expressed by MMC only, while neuregulin-1, amphiregulin and transforming growth factor-α were expressed by both MMC and normal plasma-cells. Using real-time polymerase chain reaction, we found HB-EGF, amphiregulin, neuregulin-1 and epiregulin to be expressed by cells from the bone marrow-environment. Only the EGF-members able to bind heparan-sulphate proteoglycans (HSPGs) - neuregulin-1, amphiregulin, HB-EGF - promote the growth of MMC. Those ligands strongly bind MMC through HSPGs. The binding and the MMC growth activity was abrogated by heparitinase, heparin or deletion of the HS-binding domain. The number of HS-binding EGF ligand molecules bound to MMC was higher than 105 molecules/cell and paralleled that of syndecan-1. Syndecan-1, the main HSPG present on MM cells, likely concentrates high levels of HS-binding-EGF-ligands at the cell membrane and facilitates ErbB-activation. Altogether, our data further identify EGF-signalling as promising target for MM-therapy.
Gesehen am 15.02.2022